2022
DOI: 10.3390/jcm11195698
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Parameters of Hypothermic Machine Perfusion—An Image of Initial Graft Function in Adult Kidney Transplantation?

Abstract: Kidney allografts are subjected to ischemia reperfusion injury during the process of transplantation. Hypothermic machine perfusion (HMP) of deceased donor kidneys from organ procurement until transplantation is associated with a superior outcome when compared to static cold storage (SCS). Nevertheless, cold ischemia time (CIT) remains an independent risk factor for delayed graft function (DGF) in HMP-preserved kidney allografts as well. We performed a retrospective single-center study including all adult reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The flow was consistent with our previous findings, 16 and within the range of DCD pig kidneys 28 and DBD, healthy porcine grafts. Consistently, lower flow and higher resistance were observed during HMP with 29 or without 30 oxygen. Notably, low renal arterial flow and high resistance were associated with allograft dysfunction during NMP 8 and HMP.…”
Section: Discussionsupporting
confidence: 69%
“…The flow was consistent with our previous findings, 16 and within the range of DCD pig kidneys 28 and DBD, healthy porcine grafts. Consistently, lower flow and higher resistance were observed during HMP with 29 or without 30 oxygen. Notably, low renal arterial flow and high resistance were associated with allograft dysfunction during NMP 8 and HMP.…”
Section: Discussionsupporting
confidence: 69%
“…Of these, 36 did not meet the selection criteria and were excluded. In total, there were 55 manuscripts included (N = 42 MP vs. SCS articles [ 9 , 15 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]; N = 13 NRP vs. ISP articles [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
“…There were 22 (53.7%) studies that involved kidney pairs [17,[20][21][22]24,28,[30][31][32][33][34]36,41,[44][45][46][47][48]52,57]. Studies were conducted across the world; 25 (61.0%) were single-center efforts [9,17,22,[24][25][26][27][28][29][30]35,[38][39][40][41][42][43]45,46,48,49,51,54,55,57], while 16 (39.0%) involved multiple centers [15,20,21,23,[31]…”
Section: Machine Perfusion (Mp) Vs Static Cold Storage (Scs)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increasing use of marginal kidneys, there has been a renewed interest into the use of hypothermic machine perfusion (HMP) [ 24 , 25 , 26 ]. The evidence suggests that HMP may be more beneficial in reducing delayed graft function (DGF) rates in marginal kidneys [ 27 ]. A recent study by Nath et al [ 28 ], comparing porcine kidneys’ metabolic profiles, suggested that beneficial effects exerted by HMP might be related to the removal of ROS.…”
Section: Introductionmentioning
confidence: 99%